2022
DOI: 10.1183/20734735.0172-2021
|View full text |Cite
|
Sign up to set email alerts
|

Need and baseline for harmonising nursing education in respiratory care: preliminary results of a global survey

Abstract: BackgroundThe COVID-19 pandemic confirmed that respiratory nurses are critical healthcare providers. Limited knowledge is available about appropriate education to prepare nurses to deliver high-quality respiratory care. A survey was developed by the International Coalition for Respiratory Nursing (ICRN) group to identify the need for a respiratory nursing core curriculum.MethodA 39-item survey was distributed to 33 respiratory nursing experts in 27 countries. Questions asked about current roles, perception of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Survey results confirmed a wide variation in nursing education and respiratory nursing education across the world, with many countries lacking formal educational programmes in this field and 97% reporting a need for an ICCRN. To advance this significant work, the ICRN group led by A. Šajnić and supervised by G. Narsavage plans to conduct a Delphi study to identify core curriculum requirements for respiratory nursing education at pre-registration and advanced educational levels to meet each country's specific educational requirements for recognition of respiratory nursing speciality practice [ 50 ]. Following HERMES methodology guidelines [ 51 ], S ajnic et al [ 52 ] presented the steps of the ICRN project: in 2020 experts were identified, the ICRN working group registered the Scoping Review Protocol [ 53 ], and the items obtained from this protocol will be included in the first online Delphi survey.…”
Section: Group 903: Nursesmentioning
confidence: 99%
“…Survey results confirmed a wide variation in nursing education and respiratory nursing education across the world, with many countries lacking formal educational programmes in this field and 97% reporting a need for an ICCRN. To advance this significant work, the ICRN group led by A. Šajnić and supervised by G. Narsavage plans to conduct a Delphi study to identify core curriculum requirements for respiratory nursing education at pre-registration and advanced educational levels to meet each country's specific educational requirements for recognition of respiratory nursing speciality practice [ 50 ]. Following HERMES methodology guidelines [ 51 ], S ajnic et al [ 52 ] presented the steps of the ICRN project: in 2020 experts were identified, the ICRN working group registered the Scoping Review Protocol [ 53 ], and the items obtained from this protocol will be included in the first online Delphi survey.…”
Section: Group 903: Nursesmentioning
confidence: 99%